The Secret Life of Evie Hamilton - Alliott, Catherine (London Penguin, 2009)
Evie Hamilton has a secret. One she doesn't even know about. Yet ... She's blissfully unaware that her charmed and happy life is about to be turned upside down. And it all begins one sunny, Oxford morning when a letter - a ticking time bomb - lands on Evie's immaculate doormat. Something she never anticipated threatens to sabotage all that she holds dear. It's time for her to reappraise everything in her carefully arranged universe. Is Evie strong enough to fight for what she loves? What will be left and what will change forever? And can her world really be as fragile as her best china?
Keywords: Life change events